Farmer’s Perception and Farming Practices in Rice Production under Changing Climate: Case Study in Quảng Nam Province - Minh, Ngô Đức; Trịnh, Mai Văn; Reiner, Wassmann; Hòa, Trần Đăng; Khải, Nguyễn Mạnh (VNU Journal of Science: Earth and Environmental Sciences, 2014)
Abstract: In the context of observing climate change impacts and their effect on agriculture and rice production, this study intends to assess the farmers’ perception through a study case in Quang Nam province. The social approach of climate change  vulnerability  in this case study includes defining and exploring factors that determine  farmers’ perception in four districts. Beside collection of primary and second data, key informant interviews, PRA and farm-household interviews were used for data collection. Evaluation of primary and secondary information comprised an appraisal of impacts of climate change on agriculture and livelihood of farmers, and their strategies to adapt climate change. The descriptive statistical methods were adapted, applied and used to analyse the data. The data was analysed at two scales: whole sample-level and household level. The results show the general situation of rice production under climate change conditions and its clear and considerable effects on rice cultivation in the typical regions of Quang Nam Province. Despite growing attempts of local communities and farmers’ perception to adapt to climate change and variability, further planned adaptation aimed at a larger scale and longer duration is necessary to sustain the livelihood security of smallholder farmers. Keywords : Climate change, rice production, farmer’s perception, farming practice, adaption